Manufacturing challenges and technological solutions for microwave ablation (MWA) probe prototyping. (February 2023) - Valori, Marcello; Rebaioli, Lara; Marrocco, Valeria; Modica, Francesco; Bonelli, Francesco; Pascazio, Giuseppe; Portosi, Vincenza; Prudenzano, Francesco; Fasano, Antonella; Lampignano, Vito; Fassi, Irene
In this paper, the manufacturing challenges and related technological solutions concerning the prototyping of microwave ablation (MWA) probes are addressed. In particular, the intertwined aspects pertaining probe design, fabrication and target performance are tackled. The development of a 14G MWA probe prototype, working at a frequency of 2.45 GHz, is proposed as a case study, describing design efforts and the use of rapid prototyping technologies combined with other manufacturing processes. A specific focus is dedicated to the insulating part of the probe radiating section, featuring high aspect ratio and complex shape, which was fabricated by means of Digital Light Processing (DLP) and by using a biocompatible material, the EnvisionTEC E-Shell ® 300. Furthermore, the probe handling, properly designed to arrange cables and tubes routing, was fabricated by means of Fused Deposition Modeling (FDM) technology. Finally, ex vivo experiments conducted on bovine liver showed satisfactory treatment performance and structural reliability of the 14G MWA probe prototype. Besides being characterized by a good impedance matching ( S 11 = −25 dB), prototype performance were also in good agreement with design simulations and even satisfying if compared to other results available in literature as, with an input radiation power of 40 W, the ablated zone after a 10 min treatment exhibited a ratio of the radial and longitudinal axis of 0.66.